Synen på förekomsten avhälsoproblem hos brakycefala hundar - Van Den Weghe, Johannes (Linnéuniversitetet, Institutionen för biologi och miljö (BOM), 2023)
The selective breeding of dogs (canis lupus familiaris) has a long history. Dogs thathave been bred to be brachycephalic are associated with a number of differenthealth problems such as breathing issues, problems with regulating bodytemperature and eye-, skin-, and dental disorders. A survey was used to comparedog breeder’s and clinical veterinarians’ attitudes to the prevalence of healthproblems in brachycephalic dog breeds. This study showed that there is a differencein the attitude towards health problems when comparing dog breeders andveterinarians. For most statements in the survey the dog breeders agreed to a lesserextent then the veterinarians to the health problems in their breed with the biggestdifference in the attitude towards eye-, skin- and dental disorders. This discrepancyin the answers in the survey indicates that dog breeders and veterinarians have adifferent standard for what they consider a health problem. In the long run thesedifferent standards risk to negatively affect the health of pedigree dogs.